Pautas y recomendaciones técnico-jurídicas para la configuración de un canal de denuncias eficaz en organizaciones públicas y privadas. La perspectiva española - Ballesteros Sánchez, Julio (2020)
This paper starts from a basic premise: During the last years, there have been multiple corruption cases that affected public administrations credibility, but also the one of the private sectors of the economy. Areas such as urban planning or public contracting have been prolix regarding the occurrence of criminal activities that undermine the proper functioning of the Public Administration and business activity based on ethics and mechanisms to improve organizations (public and private ones) by prematurely discovering illicit conduct and, in turn, identifying the individuals responsible for such acts. In the same way, for some companies, the verification of the effectiveness of the complaint channels in court contributes to corporate defenses and in achieving exemption from criminal responsibility. Therefore, from a technical perspective, guidelines and recommendations are offered from different regulations point of view to increase the effectiveness of these channels and to reduce the legal uncertainty that occurs in Spain, given the limited drafting of the Penal Code. Likewise, anonymity, paid denunciation and the protection of the complainant against retaliation are addressed.legality. Consequently, it is very important to implement internal complaint